Pengaruh Pemberian Air Kelapa Hijau Dalam Menurunkan Dismenore Pada Remaja PutriDi SMPN 2 Kota Bengkulu Tahun 2024 - Bagaswara, Azi; Pebriani , Emi; Susanti , Meri Epriana (CV. Utami, 2025)
Dysmenorrhea is caused by an imbalance of progesterone hormones in the blood, leading to pain. Psychological factors may also contribute to the occurrence of dysmenorrhea in some women. (Puadiah & Sutarno, 2023) According to data from the World Health Organisation (WHO) in 2020, 90% of women experience dysmenorrhea, with 10–16% experiencing severe cases. The global prevalence of dysmenorrhea is high, with approximately 50% of women worldwide experiencing menstrual pain. In Indonesia, the incidence of dysmenorrhea is very high, reaching 64.25%. 9.36% is caused by secondary dysmenorrhea, and 54.89% is caused by primary dysmenorrhea. (Azizah, 2024) This study aims to determine the effect of green coconut water on pain levels (dysmenorrhea) among female students at SMP N 2 Kota Bengkulu in 2024.The research method used was a quasi-experimental design with a one-group pretest and posttest design. The sampling technique employed in this study was total sampling, involving 21 female students experiencing dysmenorrhea. Data analysis consisted of univariate and bivariate analysis. The sample test used was the Wilcoxon test. The results of this study showed that the average mean value of dysmenorrhea pain before and after being given green coconut water was 6.63, and the average mean value of pain after being given green coconut water was 3.30. The statistical test yielded a p-value of 0.000, with a mean difference of 3.28, indicating a significant effect of green coconut water administration on adolescent girls at SMPN 2 Kota Bengkulu in 2024. The researcher recommends that the school at SMPN 2 Kota Bengkulu optimise the UKS programme services, such as providing green coconut water, which has been shown to reduce dysmenorrhea pain in adolescent girls.